Vulnerability Resilience in the Major Watersheds of the Korean Peninsula - Yong Jung; Daeun Kim; Minha Choi; Sangdan Kim; Moojong Park (Terrestrial, Atmospheric and Oceanic Sciences, 2014)

(untitled)
Water resources management requires policy enforcement in a changing environment. Climate change must be considered in major watershed river restorations in Korea. The aim of river restorations is to provide better water resource control - now and in the future. To aid in policy making in the government sector, ¡§vulnerability-resilience indexes¡¨ (VRIs) with a Delphi survey method have been adopted to provide a possible reference. The Delphi survey offers prioritized vulnerability proxy variables based on expert opinions regarding the changing environment in terms of climate change and river restorations. The VRIs of watersheds were improved after river restorations, with the exception of some locations. However, when climate change was taken into consideration in the analysis of conditions after the restorations were completed, the results showed that governments need to provide better mitigation strategies to increase vulnerability resilience in the face of climate change.